Acute hypercortisolemia inhibits innate immune parameters in Piaractus mesopotamicus experimentally infected with Aeromonas hydrophila - Cueva-Quiroz, Victor Alexander [UNESP]; Yunis-Aguinaga, Jefferson [UNESP]; Ramos-Espinoza, Fernando Carlos [UNESP]; Ruas de Moraes, Flávio; Engrácia de Moraes, Julieta Rodini [UNESP] (Elsevier, 2020)
Cortisol is a key modulator of the immune response in fish, and considered an essential molecule for adaptation of animals to stress and overcoming the stressor. Antagonist effects, pro and anti-inflammatory have been associated to acute increases in cortisol levels, however knowledge about the mechanisms of this regulation in tropical teleosts is scarce. The effects of pharmacological inhibition of cortisol release with metyrapone (MTP) on innate immune response were investigated for the freshwater teleost, Piaractus mesopotamicus, using Aeromonas hydrophila to induce an inflammatory-immune response. Pacus were randomly distributed into four experimental groups. T1: basal control, without any previous handling. T2: without MTP treatment, inoculated via swim bladder with lethal concentration 50%-96 h (LC50- 96h) of A. hydrophila. T3: supplemented with 30mgkg−1 MTP in the diet for five days, injected on the sixth day with 50mgkg−1 live weight (LW) MTP and immediately inoculated with the bacteria. T4: supplemented with MTP, without bacterial inoculation. Blood samples were taken at 1, 3, 6 and 9 h post infection (hpi), for assessment of cortisolemia, glycemia, hematological and innate immunity parameters. The results revealed that high cortisol concentrations, during the initial phase of A. hydrophila infection, inhibited the immune-inflammatory response. Fish treated with MTP and inoculated with the bacterium showed significant higher total blood leukocytes and lymphocytes numbers, blood phagocyte respiratory activity and plasma lytic activity when compare to infected fish that did not receive MTP. It was concluded that the inhibition of cortisol release favored the immune-inflammatory response during the initial phase of bacterial infection.
Keywords: Cortisol; Inflammation; Metyrapone; Pacu; Sepsis